cJun NH(2)-terminal kinase mediates Interleukin-1β induced inhibition of lacrimal gland secretion. - Zoukhri, Driss (2005)
Sjögren’s syndrome (SS), an inflammatory disease affecting the lacrimal and salivary glands, is the leading cause of aqueous tear-deficient type of dry eye. We previously showed that IL-1β protein is up regulated in the lacrimal gland of a murine model of SS and that exogenous addition of this cytokine inhibits neurotransmitter release and lacrimal gland protein secretion. In the present study we investigated the role cJun NH2-terminal kinase (JNK) in IL-1β mediated inhibition of lacrimal gland secretion and tear production. In vitro, IL-1β induced a time-dependent activation of JNK with a maximum 7.5-fold at 30 min. SP600125, a JNK inhibitor, inhibited, in a concentration-dependent manner, IL-1β induced activation of JNK with a maximum of 87% at 10(-4) M. In vivo, IL-1β stimulated JNK and the expression of the inducible isoform of nitric oxide synthase (iNOS). IL-1β inhibited high KCl and adrenergic agonist induced protein secretion by 85% and 66%, respectively. SP600125 alleviated the inhibitory effect of IL-1β on KCl- and agonist-induced protein secretion by 79% and 47%, respectively and completely blocked the expression of iNOS. Treatment for 7 days with SP600125 increased tear production in a murine model of SS dry eye. We conclude that JNK plays a pivotal role in IL-1β mediated inhibition of lacrimal gland secretion and subsequent dry eye.